Krisis kepercayaan masyarakat terhadap demokrasi Indonesia - Saputra, Muhammad Ferdyansyah (Maliki Interdisciplinary Journal, 2026)
Democracy is a system of government that places the people as the highest holders of sovereignty in state administration. However, in its development, Indonesian democracy faces significant challenges, particularly the declining level of public trust in democratic institutions and practices. This study aims to analyze the condition of the public trust crisis in Indonesian democracy, identify its contributing factors, and examine strategies to restore public confidence. The research employs a library research method by reviewing various academic journals, books, and other relevant literature related to democracy and public trust. The findings indicate that the crisis of trust is characterized by increasing political apathy, declining confidence in state institutions, and growing social and political polarization. The factors contributing to this condition include corruption, vote-buying practices, abuse of power, weak law enforcement, the spread of misinformation and disinformation, and socio-economic inequality. To address these challenges, efforts are needed to strengthen governmental transparency and accountability, reform political and legal institutions, combat corruption, improve political education and digital literacy, and expand public participation in democratic processes. Therefore, restoring public trust is a crucial step toward building a more inclusive, accountable, and high-quality democracy in Indonesia.